Asset market participation, monetary policy rules and the great inflation - Florin O. Bilbiie; Roland Straub (European Central Bank (ECB), 2012)
This paper argues that limited asset market participation is crucial in explaining U.S. macroeconomic performance and monetary policy before the 1980s, and their changes thereafter. In an otherwise conventional sticky-price model, standard aggregate demand logic is inverted at low enough asset market participation: interest rate increases become expansionary; passive monetary policy ensures equilibrium determinacy and maximizes welfare. This suggests that Federal Reserve policy in the pre-Volcker era was better than conventional wisdom implies. We provide empirical evidence consistent with this hypothesis, and study the relative merits of changes in structure and shocks for reproducing the conquest of the Great Inflation and the Great Moderation.
Keywords: E31; E32; E44; E52; 330; Great Inflation; Great Moderation; limited asset markets participation; passive monetary policy rules; Geldpolitik; Regelbindung versus Diskretion; Inflation; Wertpapierhandel; USA